Analisis Srategi Pemasaran Digital pada UMKM Macarina (Macaroni Nagih) di Kabupaten Jember - Aprilia Eka Nurcahyanti (Fakultas Ilmu Sosial dan Ilmu Politik, 2025)
The development of digital technology has changed the marketing strategies of business actors, where digital marketing is now the main strategy in facing increasingly competitive market competition. Macarina is a flagship product of CV Macarindo Berkah Group, a company engaged in the food and beverage sector with a focus on the production of processed snacks made from macaroni. Since its inception, this company has followed technological developments by implementing digital marketing strategies to expand its market reach. The purpose of this study is to analyze and describe the digital marketing strategy implemented by Macarina. This study uses a descriptive qualitative approach with data sourced from observation, interviews and documentation. The results of the study show that the management of Macarina's digital marketing strategy is carried out through three stages including planning, implementation, and evaluation. The marketing media used by Macarina include Instant Messaging Marketing by sending short messages in the form of birthday greetings and the latest discount offers to customers via WhatsApp and Instagram Direct Message. Search Engine Marketing (SEM) with the use of paid advertising through Bing ads and Shopee ads. Social Media Marketing (SMM) promotes through social media WhatsApp, Facebook, Youtube and Instagram. Content Marketing through video content uploaded on Instagram Reels and Youtube. Search Engine Optimization (SEO) optimization through SEO Off Page with publication in news media and SEO On Page through keyword settings in product titles and descriptions in the Shopee marketplace. Finally, Online Food Delivery (OFD) using the ShopeFood, GoFood, and GrabFood applications. Macarina can continue to develop her business by using other digital platforms and utilizing the features available in them.
Entry oleh Arif 2026 Maret 25
Keywords: Strategy Management; Instant Messaging Marketing; Search Engine Marketing; Social Media Marketing; Content Marketing; Search Engine Optimization; Online Food Delivery